Whole mitochondrial genomes illuminate ancient intercontinental dispersals of grey wolves (Canis lupus). (22nd June 2016) - Koblmüller, Stephan; Vilà, Carles; Lorente‐Galdos, Belen; Dabad, Marc; Ramirez, Oscar; Marques‐Bonet, Tomas; Wayne, Robert K.; Leonard, Jennifer A.
Abstract: Aim: Grey wolves ( Canis lupus ) are widespread across the Holarctic. Here, we test the previously proposed hypothesis that extant North American wolves originate from multiple waves of colonization from Asia. We also test the hypothesis that land connections have been important in the evolutionary history of other isolated wolf populations in Japan. Location: Holarctic. Methods: We analyse 105 previously published and newly obtained complete mitochondrial genomes from a geographically diverse sample of grey wolves and date critical branches in the phylogenetic tree. Phylogeographical hypotheses are tested in an approximate Bayesian computation approach. Results: We find that the mitogenomes of all living wolves in North America, including Mexican wolves, most likely derive from a single colonization event from Eurasia that expanded the grey wolf range into North America. This colonization occurred while a land bridge connected Eurasia and North America before the Cordillerian and Laurentide ice sheets fused in the Last Glacial Maximum, c . 23 ka, much more recent than predicted based on the fossil record. Pleistocene land bridges also facilitated the separate colonization of Hokkaido and the southern Japanese islands. Main conclusions: Extant wolf lineages in North America derive from wolves that migrated into North America coincident with the formation of the most recent land bridge with Eurasia. The maternal lineages from earlier Pleistocene American wolves are not represented in living American wolves, indicating that they left no descendants. The timing of colonization of North America, Hokkaido and the southern Japanese islands corresponds to the changes in land connectivity as a consequence of changing sea level.